(untitled) (The Review of Diabetic Studies, 2024)
Hypertension is a leading global risk factor for cardiovascular disease, contributing significantly to morbidity and mortality worldwide. While traditional mechanisms such as the renin–angiotensin–aldosterone system, sympathetic nervous system activation, and renal dysfunction are well recognized, increasing evidence highlights oxidative stress and inflammation as key contributors to the pathogenesis of hypertension. Oxidative stress results from an imbalance between the generation of reactive oxygen species and antioxidant defense mechanisms, leading to reduced nitric oxide bioavailability, endothelial dysfunction, vascular remodeling, and arterial stiffness. Concurrently, chronic low-grade inflammation characterized by immune cell activation and elevated levels of pro-inflammatory cytokines, including tumor necrosis factor-α, interleukin-6, and interleukin-17, further exacerbates vascular injury and blood pressure elevation. These processes are closely interconnected, forming a self-amplifying cycle in which oxidative stress promotes inflammation and inflammatory pathways enhance reactive oxygen species production. This interaction plays a central role in the initiation, maintenance, and progression of hypertension and its associated target-organ damage. Understanding the molecular and cellular mechanisms underlying the oxidative stress–inflammation axis provides valuable insights into disease development and highlights potential therapeutic targets. Interventions targeting these pathways, including renin–angiotensin–aldosterone system inhibitors, antioxidants, anti-inflammatory agents, and lifestyle modifications, may offer improved strategies for hypertension prevention and management. This review summarizes current evidence on the role of oxidative stress and inflammation in hypertension and discusses their clinical and therapeutic implications.